Snake-Search Bot: Design of Autonomous Search Robot for SAR Aid Process of Earthquake Victims (LACCEI, 2024)
Abstract— This paper displays the description, design, and features of the Snake-Search Bot. A search robot is a robotic device used to locate people in danger or distress after a natural disaster —in this case an earthquake has occurred. This is an autonomous, low-cost, snake-like robot intended to go into the debris caused by earthquakes to identify human bodies trapped beneath, gather the data, and send the signals to a rescue team. This robot will use sensors for human life identification it will then send alerts to the software for the rescue team to get updates on what is happening between the debris. The robot will also project a mapping system (SLAM) to facilitate the rescue process. This project is targeted at Latin American countries, especially those most prone to earthquakes such as Mexico, Guatemala, Chile, and Peru. The robot was programmed with python on a Raspberry Pi and includes the following cameras and sensors: a thermal camera, night vision camera, TF Luna LiDAR, an inertial sensor, encoder motors, seed MRH60, microphone, and speaker.